Weaning Ventilator pada Pasien Tetraparese Neglecteed Cervical Spondiloptosis dengan Dislokasi Faset Bilateral Cervical 5-6 dan Spinal Cord Injury Inkomplet Level Cervical 6 - Sudadi; Rahardjo, Sri; Suharso, Pamungkas Hary (Jurnal Komplikasi Anestesi, 2021)
The patient is a 16 year old male who suffered a cervical injury due to a slipping fall. Pain was felt in the neck, followed by weakness in the limbs, but did not immediately go to the hospital. The patient was referred to Sardjito Hospital about 1 month after the incident, with examination at the previous hospital the patient had a cervical injury with tetraparesis.The patient underwent corpectomy, decompression, and stabilization surgery on the second day. Postoperatively the patient was admitted to the ICU. On the second day of treatment, extubation was carried out, but was later re-intubated because the patient had respiratory distress. The next therapy was physiotherapy, nebulizer and mucolytic, ventilator weaning with pressure support mode and progressive ventilator free breathing (PVFB), Percutaneous Dilatation Tracheostomy (PDT), nutritional therapy, analgesics and antibiotics. On the way, the patient experienced pulmonary atelectasis, sepsis, and several failures in the ventilator weaning trial, so PDT was performed. The patient then experienced an improvement in his condition which was characterized by an increase in lung capacity, extremity muscle strength, and improvement in the condition of sepsis. Until finally the patient was able to be released from the use of the ventilator on the 15th day of treatment by using a T-piece through atracheostomy tube.